A spirometric journey following lung transplantation. Issue 3 (3rd September 2014) - Fuller, Jeremy; Paraskeva, Miranda; Thompson, Bruce; Snell, Greg; Westall, Glen
Abstract Spirometry is regarded as the primary tool for the evaluation of lung function in lung transplant (LTx) recipients. Spirometry is crucial in detecting the various phenotypes of chronic lung allograft dysfunction (CLAD), including restrictive allograft syndrome (RAS) and bronchiolitis obliterans syndrome (BOS) – note that these phenotypes potentially have different etiologies and therapies. Following LTx for idiopathic pulmonary fibrosis, a 60‐year‐old male recipient's lung function began to gradually improve, peaking at 5 months post‐LTx. Subsequently, with increasing impairment of graft function, the diagnosis of BOS was made. A second LTx was performed and lung function subsequently began to increase again. Unfortunately, another year on, lung function deteriorated again – this time due to the development of RAS, antibody‐mediated rejection was implicated as the possible underlying cause. This case report highlights the importance of spirometry in assessing the patterns of CLAD following LTx.